ANALISIS PENGENDALIAN KUALITAS PRODUK SARI ROTI SELAI NANAS MENGGUNAKAN STATISTICAL QUALITY CONTROL - Sukmawati, Sri; Huda, Miftahul; Panulisan, Bambang Setyo; Mahardika, Angga Roby (LPPM Universitas Bina Bangsa, 2023)
PT Nippon Indosari Corpindo, Tbk is one of the largest bread companies with the Sari Roti trademark in Indonesia. Based on the results of observations and data obtained at the Production Department, it was found that bread products from various bread variants were found to produce pineapple jam bread every day producing +/- 2000 pcs/day. There were still defects found in 2.88% of the total production. This research uses a quantitative approach with the data processing analysis used is the Statistical Quality Control (SQC) method. The research results show that controlling production quality in an effort to reduce the number of defects in pineapple jam bread products at PT. Nippon Indosari Corpindo, Tbk, using the Statistical Quality Control method, can determine defects that occur using the Pareto diagram to find the cause of the number of defects in pineapple jam bread products, the most dominant of which is stiff/does not rise with a total of 34.59%. From the fishbone diagram, it can be seen that defects in pineapple jam bread products are caused by human factors that are less careful, and also by machine factors whose standard usage exceeds the standard limits